2018
DOI: 10.2478/johr-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Storage and Quality of Apples ‘Reinette Simirenko’, Depending on the Dose of Post-Harvest Treatment with Ethylene Inhibitor 1-MCP

Abstract: Natural weight losses, flesh and core browning, senescent breakdown and fruit rot, ethylene-production, firmness, soluble solids content, titratable acidity and taste of apple ‘Reinette Simirenko’ during storage, depending on the dose of postharvest treatment with 1-methylcyclopropene (1-MCP) were studied. Fruits were collected in harvesting maturity and treated with 1-MCP at the recommended dose of 1000 ppb (SmartFreshTM 0.068 g·m−3) and experimental doses of 750 ppb (75% of the recommended dose) and 500 ppb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Regarding apple fruit, if the harvest time is delayed, the firmness of the fruit decreases (Shafiq et al., 2011); however, the percentage loss during storage to be cultivar and storage technology dependent (Juhņeviča‐Radenkova & Radenkovs, 2016a; Radenkovs & Juhnevica‐Radenkova, 2018). A positive effect of 1‐MCP on flesh firmness of apple (Melnyk et al., 2019), pear (Mahajan et al., 2010), cherry tomato (Taye et al., 2019), and many other fruit and vegetables has been broadly documented. Moreover, affirmative results were also reported on CA storage for apple (Juhņeviča‐Radenkova & Radenkovs, 2016b), pear (de Martin et al., 2017) medlar (Selcuk & Erkan, 2015), and lemon (Ma et al., 2019) fruit.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding apple fruit, if the harvest time is delayed, the firmness of the fruit decreases (Shafiq et al., 2011); however, the percentage loss during storage to be cultivar and storage technology dependent (Juhņeviča‐Radenkova & Radenkovs, 2016a; Radenkovs & Juhnevica‐Radenkova, 2018). A positive effect of 1‐MCP on flesh firmness of apple (Melnyk et al., 2019), pear (Mahajan et al., 2010), cherry tomato (Taye et al., 2019), and many other fruit and vegetables has been broadly documented. Moreover, affirmative results were also reported on CA storage for apple (Juhņeviča‐Radenkova & Radenkovs, 2016b), pear (de Martin et al., 2017) medlar (Selcuk & Erkan, 2015), and lemon (Ma et al., 2019) fruit.…”
Section: Resultsmentioning
confidence: 99%
“…The level of senescent breakdown at the end of storage in the control fruit for 'Orchard 2 was similar to the results found by Wang and Sugar [49] for pear cv. 'Bartlett' (38.3%), by Wang and Sugar [50] for 'Doyenne du Comice' after 4 and 6 months, respectively, of cold storage in air plus 5 days of ripening or by Melnyk et al [17], who found losses of 44.4% in apple cv. 'Reinette Simirenko' after seven months of storage due to senescent breakdown.…”
Section: Discussionmentioning
confidence: 96%
“…Some authors claim that almost all pre-harvest factors that influence the incidence of bitter pit in apple fruit can be directly or indirectly related to the fruit's calcium nutrition [11]. Senescent breakdown is also due to a nutritional disorder in the orchard [12], but other key factors contribute to the outbreak of this disorder, such as tree age, pruning, fruit maturity, fruit size, storage temperature and storage period [12][13][14][15]; therefore, after long storage periods, and after simulated shelf life, these disorders limit the storage length up to 5-6 months [14,16,17].…”
Section: Introductionmentioning
confidence: 99%